Culture-Dependent and -Independent Characterization of Microbial Communities Associated with a Shallow Submarine Hydrothermal System Occurring within a Coral Reef off Taketomi Island, Japan - Hirayama, Hisako (American Society for Microbiology (ASM), 2007)
Microbial communities in a shallow submarine hydrothermal system near Taketomi Island, Japan, were investigated using cultivation-based and molecular techniques. The main hydrothermal activity occurred in a craterlike basin (depth, ∼23 m) on the coral reef seafloor. The vent fluid (maximum temperature, >52°C) contained 175 μM H(2)S and gas bubbles mainly composed of CH(4) (69%) and N(2) (29%). A liquid serial dilution cultivation technique targeting a variety of metabolism types quantified each population in the vent fluid and in a white microbial mat located near the vent. The most abundant microorganisms cultivated from both the fluid and the mat were autotrophic sulfur oxidizers, including mesophilic Thiomicrospira spp. and thermophilic Sulfurivirga caldicuralii. Methane oxidizers were the second most abundant organisms in the fluid; one novel type I methanotroph exhibited optimum growth at 37°C, and another novel type I methanotroph exhibited optimum growth at 45°C. The number of hydrogen oxidizers cultivated only from the mat was less than the number of sulfur and methane oxidizers, although a novel mesophilic hydrogen-oxidizing member of the Epsilonproteobacteria was isolated. Various mesophilic to hyperthermophilic heterotrophs, including sulfate-reducing Desulfovibrio spp., iron-reducing Deferribacter sp., and sulfur-reducing Thermococcus spp., were also cultivated. Culture-independent 16S rRNA gene clone analysis of the vent fluid and mat revealed highly diverse archaeal communities. In the bacterial community, S. caldicuralii was identified as the predominant phylotype in the fluid (clonal frequency, 25%). Both bacterial clone libraries indicated that there were bacterial communities involved in sulfur, hydrogen, and methane oxidation and sulfate reduction. Our results indicate that there are unique microbial communities that are sustained by active chemosynthetic primary production rather than by photosynthetic production in a shallow hydrothermal system where sunlight is abundant.